Evaluating car centre service quality with modified Kano model based on the first-time buyer's age - Yen Hsun Chen; Ying Liang Chou; Chung Lin Tsai; Han Chao Chang (Cogent Business & Management, 2018)
Modified Kano models, proposed by Prof. Matzler and Hinterhuber, are mostly applied to the qualitative analysis of performance indicators, but have not been used to validate the theoretical hypothesis of customer's quantitative studies. In this study, regression analysis has been used to analyse the correlation between service quality (by SERVQUAL) and customer loyalty in car service centres, and then quality ingredients of modified Kano model have been encoded to determine whether the statistical values accorded with F-distribution and Scheffe's post hoc analysis were used to confirm the Kano model's possibilities in quantitative research. The results of regression analysis show that different aged customers have different views on loyalty, each factor of the SERVQUAL scale has a significant relevance on customer loyalty in the >30-year-old group. However, in the <30 group, there is no significant correlation between responsiveness and customer loyalty. The F-test results show that there are significant differences in SERVQUAL's tangibles, reliability and empathy factors. Scheffe's post hoc analysis shows the significance in these three factors. Therefore, this study confirms that the Kano model also can verify the hypothesis of quantitative research and test research models after summarising and encoding the quality elements of the question items contained in effective questionnaires.
Keywords: 650